2010
DOI: 10.1002/chp.20050
|View full text |Cite
|
Sign up to set email alerts
|

The growth, characteristics, and future of online CME

Abstract: Online CME use is growing rapidly and is likely to be half of all CME consumed by practicing physicians within a few years. The pattern is consistent with Christensen's model of "disruptive innovation," whereby an innovative technology eventually displaces an incumbent technology by first providing a relatively low-quality, low-cost product that meets the needs of unserved customers. The technologies being developed for online CME may facilitate broader changes in medical education as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 10 publications
1
47
0
5
Order By: Relevance
“…11 The Internet's potential for delivering online and computer-based electronic CME (eCME) is great, 12 and eCME has been increasingly explored, evaluated, and validated as an effective learning modality.…”
Section: Background and Purposementioning
confidence: 99%
“…11 The Internet's potential for delivering online and computer-based electronic CME (eCME) is great, 12 and eCME has been increasingly explored, evaluated, and validated as an effective learning modality.…”
Section: Background and Purposementioning
confidence: 99%
“…-la littérature générale en matière de formation sur Internet et d'information en santé [2,6,7,8,9,13] ; -les lignes directrices du développement professionnel continu (DPC) du Conseil québécois de déve-loppement professionnel continu des médecins (CQDPCM) [10] ; -l'expérience personnelle en DPC des membres du comité de la recherche en FPC de Médecins francophones du Canada.…”
Section: Construction De La Grille D'évaluation Et Sélection De Sitesunclassified
“…An online format offers several important advantages over traditional CME, including ease of access, flexible timing, low cost and potentially enhanced effectiveness (2). Because of these advantages and its consequent rise in popularity, online CME is considered to be a major innovation that could lead to abandonment of traditional face-to-face CME programs (3). Investigation of online CME in 2008 found that there was a rapid increase in online CME, but it still amounted to only 6.9% to 8.8% of all CME available.…”
mentioning
confidence: 99%
“…Investigation of online CME in 2008 found that there was a rapid increase in online CME, but it still amounted to only 6.9% to 8.8% of all CME available. The authors predicted exponential growth in the next few years, with up to 50% of CME being delivered online by 2015 (3).…”
mentioning
confidence: 99%